A study on service quality of refurbishment contractors towards clients at public institutions of higher education / Sallehan Ismail, Mohamad Hamdan Othman and Sufian Che Amat - Ismail, Sallehan; Othman, Mohamad Hamdan; Che Amat, Sufian (2010)
The market for construction refurbishment work will continue to grow steadily over this decade, and this will provide many opportunities for contractors. However, local contractors face several issues in the refurbishment market today. The construction industry is characterized as fragmented and highly competitive. In this regard, contractors must bank on the value of customer service to address this problem. Delivering quality service is recognized as a new strategy for contractors to stay ahead of the competition. This study aims to examine contractors' service quality performance and to explore the relationship between service quality and client satisfaction when undertaking refurbishment projects for public institutions of higher education in Malaysia. Data were collected through a structured questionnaire. The questionnaire was generated based on the five service quality determinants in SERVQUAL (Parasuraman et al., 1988), namely, reliability, responsiveness, assurance, empathy, and tangibles. From these five determinants, thirty-two attributes that may affect project service quality in refurbishment projects are identified to ascertain clients' service quality expectations. The results indicate that the reliability factor is the most important variable of service quality and that clients at public institutions of higher education have high expectations in terms of service quality from refurbishment contractors.